B cells and Antibodies in the Defense against Mycobacterium tuberculosis infection - Achkar, Jacqueline M. (Immunol Rev, 2015)
Better understanding of the immunological components and their interactions necessary to prevent or control Mycobacterium tuberculosis (Mtb) infection in humans is critical for tuberculosis (TB) vaccine development strategies. While the contributory role of humoral immunity in the protection against Mtb infection and disease is less defined than the role of T cells, it has been well established for many other intracellular pathogens. Here we update and discuss the increasing evidence and the mechanisms of B cells and antibodies in the defense against Mtb infection. We posit that B cells and antibodies have a variety of potential protective roles at each stage of Mtb infection, and postulate that such roles should be considered in the development strategies for TB vaccines and other immune-based interventions.